2012
DOI: 10.1017/s1047951112000765
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular-associated tracheobronchial obstruction in children

Abstract: Tracheobronchial compression of cardiovascular origin is an uncommon and frequently unrecognised cause of respiratory distress in children. The compression may be due to encircling vessels or dilated neighbouring cardiovascular structures. Bronchoscopy and detailed radiography, especially computed tomography and magnetic resonance imaging, are among the most powerful diagnostic tools. Few previous reports have addressed the relationship between bronchoscopic findings and underlying cardiovascular anomalies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…8 Previous studies have demonstrated that the incidence of tracheal compression among patients with congenital heart disease is higher than that among other populations. 9 The tracheal or bronchial compression in some patients is caused by an increase in the pulmonary artery diameter. Therefore, the right pulmonary artery is placed in the forward position or the pulmonary artery wall is folded to relieve this compression.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have demonstrated that the incidence of tracheal compression among patients with congenital heart disease is higher than that among other populations. 9 The tracheal or bronchial compression in some patients is caused by an increase in the pulmonary artery diameter. Therefore, the right pulmonary artery is placed in the forward position or the pulmonary artery wall is folded to relieve this compression.…”
Section: Discussionmentioning
confidence: 99%